Practical implementation of the Niederreiter modified cryptocode system on truncated elliptic codes - Yevseiev, Serhii; Tsyhanenko, Oleksii; Ivanchenko, Serhii; Aleksiyev, Volodymyr; Verheles, Dmytrо; Volkov, Sergey; Korolev, Roman; Kots, Hryhorii; Milov, Oleksandr; Shmatko, Olexander (Eastern-European Journal of Enterprise Technologies, 2018)
On the basis of the practical implementation of the classic Niederreiter scheme for non-binary codes, a pattern has been identified for practical implementation –fixing the admissible position vectors of the plaintext transformation based on equilibrium coding. The obtained set of position vectors of the error vector with a fixed set of masking matrices (the recipient's private key) allows us to obtain the algorithm for decoding the classical Niederreiter crypto-code scheme on non-binary codes. For this, a modification of the crypto-code system (CCS) is necessary. It is proposed to use the additional parameter of key data – the initialization vector (the set of invalid position vectors of the error vector). To counter the Sidelnikov attacks, it is proposed to use modified (shortened) algebraic-geometric (elliptic) codes (MEC). For this, it is necessary to use the second additional initialization vector (the set of positions for shortening the error vector). Based on the modification of the classical Niederreiter scheme on non-binary codes, applied algorithms for generating and decrypting a cryptogram in the Niederreiter modified crypto-code system based on modified (shortened) elliptic codes and software are proposed. To confirm the profitability of the proposed crypto-code system, the results of the comparative evaluation of energy consumption for the implementation of the classical Niederreiter scheme on elliptic codes and the implementation of the proposed system on modified elliptic codes are presented. The results confirm the possibility of practical implementation of the Niederreiter crypto-code system based on the proposed algorithms. At the same time, the required level of cryptographic strength of the crypto-code system, protection of the cryptosystem against the Sidelnikov attacks and an increase in the rate of cryptographic transformations by 3-5 times compared with the classical Niederreiter scheme are guaranteed